Merajut Kearifan Lokal dan Global dalam Bahan Ajar Digital Multimodal Cerita Pendek untuk Kelas XI - Fatihatur Rachmah; Werdiningsih, Dyah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to develop multimodal digital teaching materials for short story learning that incorporate elements of local and global wisdom for grade XI students at the Islamic Senior High School (MA). This research is a type of Research and Development (R&D). The development method used is Design and Development Research (DDR), which has been adapted to the scope of the study into two stages: the preliminary stage and the design stage. The study was conducted at MA Al-Huda Sumber Nangka. The data were obtained from interviews with the Indonesian language teacher and student questionnaires to determine the students’ needs and learning characteristics. The results of the exploration stage revealed that the teaching materials used by the teacher were printed textbooks. The student questionnaires showed a lack of interest in short story learning, despite the students’ diverse learning characteristics. The design stage involved developing multimodal teaching materials consisting of text, illustrated text, audiovisual content, gamification and flipbook. Elements of local and global wisdom were integrated into the short story examples, such as works by Seno Gumira Ajidarma and Raditya Dika.